A Futuristics Pyrolysis Technique: Conversion of Waste Plastic Polybags Into Fuel - Meghna Chaudhary; Monika (International Journal of Advance in Molecular Engineering, 2025)
Plastics are high molecular weight materials composed of repeating polymer units and can be classified based on factors like chemical composition, structure, stiffness, application types, and processing methods. A key environmental issue with plastics is their non-biodegradability, causing them to persist in the environment. Pre-consumer plastic waste includes manufacturing defects, rejected items, and excess materials produced during virgin plastic manufacturing. In India, around 15,342 tons of plastic waste are collected daily, highlighting the urgency of the problem. Recycling remains a common but largely ineffective method due to the challenges of cleaning and segregating plastics. Globally, over 100 million tons of plastic are produced annually, with plastic waste filling landfills and acting as carbon sinks, trapping CO₂. Disposal methods like incineration and gasification are criticized for releasing toxic gases and being costly. Pyrolysis stands out as a promising solution, involving the thermal decomposition of plastics into fuel-range hydrocarbons like petrol, diesel, and kerosene. The process involves catalytic cracking at high temperatures, where the resulting gases are condensed to produce liquid fuels. The efficiency of this method depends on the type of plastic used, with some yielding better fuel conversion rates. Compared to traditional disposal methods, pyrolysis offers significant environmental advantages by reducing plastic waste and conserving petroleum resources. As this technology advances, it holds the potential to become a pivotal solution for managing the global plastic waste crisis.
Keywords: CFD; HDPE; LDFE; OD; PET; PP; PVC